Femtosecond laser micro-milling dental glass ceramics: An experimental analysis and COMSOL finite element simulation. Issue 14 (1st October 2020) - Hu, Peixin; Yao, Lu; Zhang, Mingji; Nie, Zilin; Ji, Encai; Lue, QiTao; He, Zhengdi
Abstract: Dental glass ceramic materials are widely used in all-ceramic restoration technology. In order to effectively solve the problems existing in the process of traditional diamond cutter milling dental glass ceramic materials, such as severe needle loss, large tool wear and general milling efficiency, a new method of ultrafast laser milling dental glass ceramics is proposed. In this paper, 1030 nm femtosecond laser with pulse width of 600fs was used to micro-mill dental glass ceramics. Confocal laser microscopy was used to measure the milling depth and surface roughness of single-layer milling under selected laser processing parameters. The pre-layered milling software was developed to control the z-axis lifting and to compensate the focal length synchronously. Scanning electron microscope (SEM), Raman spectrometer and Vickers micro-hardness tester were used to characterize the dental glass ceramics after femtosecond laser milling. The results showed that under the specific laser processing parameters, the infrared femtosecond laser milling system can achieve a good processing morphology without changing the surface composition and surface hardness of dental glass ceramics. This new dental glass ceramics processing method based on ultrafast laser technique indicated a new direction for further chair processing of dental all-ceramic restoration technology.